Study on Strategic HR Roles in India: HR Dares to be the Think Tank: Exploring the Link between Strategic HR Roles, Organizational Learning, and Risk Management in India (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The global business is likewise inclined to various risks like political hazard, money chance, organization risks etc. HR is required to perform at all operational levels over all specialty units be it household or global. In such conditions, the risk of organization inconsistencies is unavoidable. The aim of this paper is to discover analysis of strategic HR roles and organizational learning capability.